Spiralling whitefly, Aleurodicus dispersus, a recent invader and new cassava pest - Neuenschwander, Peter (1994)
The spiralling whitefly, Aleurodicus dispersus Russell (Hom., Aleyrodidae), a native of Central America, was found in continental Africa for the first time early in 1992, and has since spread to five West and Central African countries. It is a polyphagous pest which causes substantial damage also on cassava. In mid-1993, two parasitoids, Encarsia sp. near haitiensis Dozier and E. guadeloupae Viggiani (Hym., Aphelinidae) were recovered from A. dispersus in Benin. They probably had arrived serendipitously. Wherever the whitefly spreads, initially damaging populations were observed. In coastal Benin, population levels declined sharply in 1994. The necessity of introducing another biological control agent, the predator Nephaspis oculatus Blatchley (=amnicola Wingo) (Col., Coccinellidae), remains therefore unclear.